2009
DOI: 10.1128/iai.00013-09
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogenic Escherichia coli -Induced Inflammation Alters Mouse Urinary Bladder Contraction via an Interleukin-6-Activated Inducible Nitric Oxide Synthase-Related Pathway

Abstract: Escherichia coli is the most common cause of urinary tract infection. Elevated blood and urine interleukin-6 (IL-6) levels have been shown in inflammatory urinary tract diseases. The role of IL-6 in mediating the urodynamic dysfunction in response to E. coli-induced urinary tract infection has not yet been fully elucidated. In this study, we investigated the role of IL-6 in the nitric oxide (NO)-triggered alteration of contractile responses in the urinary bladder under an E. coli-induced inflammatory condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…;220 Muscle-derived IL-6 expression within the contracting muscle increases in response to a reduction of intramuscular glycogen content, suggesting that the IL-6 response may be a signal that muscle glycogen stores are being depleted 221222 We report significantly higher myometrial IL-6 mRNA and protein expressions in an arrest of descent compared to spontaneous term labor.…”
Section: Commentmentioning
confidence: 81%
“…;220 Muscle-derived IL-6 expression within the contracting muscle increases in response to a reduction of intramuscular glycogen content, suggesting that the IL-6 response may be a signal that muscle glycogen stores are being depleted 221222 We report significantly higher myometrial IL-6 mRNA and protein expressions in an arrest of descent compared to spontaneous term labor.…”
Section: Commentmentioning
confidence: 81%
“…22 Furthermore, IL-6 can enhance detrusor smooth muscle contractility, which might result in voiding frequency. 23,24 Lamale et al 13 reported that IL-6 levels increased in patients with IC versus controls, and Erickson et al 12 confirmed this observed correlation between IL-6 and IC, further establishing an association between IL-6 and symptom severity. Peters et al reported that IL-6 levels were elevated in active IC, and patients with IC in remission after receiving BCG had identical IL-6 levels and symptom scores as non-IC control subjects.…”
Section: Discussionmentioning
confidence: 93%
“…IL‐6 is important to the transition between acute and chronic inflammation, and exhibits a pro‐inflammatory profile in chronic inflammation . Furthermore, IL‐6 can enhance detrusor smooth muscle contractility, which might result in voiding frequency . Lamale et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, E. coli-induced bladder inflammation was associated with an increased bladder contractile response, which was mediated by the NO-induced activation of PKC (44). Given that GJs are required for the coordinated contractile response (45), the elevation of Cx43 by NO in BSMCs could exaggerate the abnormal bladder contractile response under inflammatory situations.…”
Section: Discussionmentioning
confidence: 98%